Implementasi Peraturan Menteri Agraria dan Tata Ruang Nomor 6 Tahun 2018 di Kabupaten Asahan - Monalisa Aritonang; Budi Hartono; Isnaini Isnaini (Mahesa Research Center, 2022)
This study aims to reveal, examine and analyze the implementation and obstacles to the implementation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration in Asahan Regency. This type of research is descriptive qualitative research, which aims to reveal the problem or situation as it is or based on the existing facts. Data collection techniques used in this study were interviews and observations. Research informants were selected by purposive sampling. The results of the study found that in terms of communication it has been going well; In terms of resources, the ability of the HR appointed as the PTSL Task Force is quite good. All officers have a high commitment to the successful implementation of PTSL in Asahan District; In terms of the bureaucratic structure has been going well. The obstacles faced by agencies in implementing the Regulation of the Minister of Agrarian and Spatial Planning/Head of the Republic of Indonesia are the lack of human resources, facilities and infrastructure and the low interest of the people of Asahan district to participate in the PTSL program.